The Effect Of Product Quality, Price, And Innovation On Marketing Performance Moderated Consumer Purchasing Power In UMKM Of Boba Drinks In Deli Serdang - Tirtayasa, Satria (Publisher Cv. Inara, 2022)
The purpose of this study was to see the effect of product quality, price, and innovation on marketing performance moderated by the purchasing power of consumers in UMKM of Boba Drinks in Deli Serdang. This study uses an associative research approach. The population of this study is all the users of UMKM in the beverage sector (especially beverage Boba) in the District of Deli Serdang. The population in this research does not know certain, and the sample in this study takes 100 UMKM Boba Drinks based on the Lemeshow formula. Sample of 100 UMKM boba drinks. in the District of Deli Serdang distributed in districts located in urban areas, district Kec. Tanjung Morawa, District.Percut Sei Tuan, District .Sunggal, District. Lubuk Pakam, District. Labuhan Deli. Each city took 20 UMKM as a sample. Hypothesis test in this research using regression hierarchy. Based on the results of research product quality affects the marketing performance of UMKm Boba Drinks in Deli Serdang regency. Price affects the marketing performance of B UMKM Boba Drinks in Deli Serdang regency. Innovation affects the marketing performance of UMKM Boba Drinks in Deli Serdang regency. Purchasing ability can moderate the influence of product quality on the marketing performance of UMKM Boba Drinks in Deli Serdang regency. Purchasing ability can moderate the influence of prices on the marketing performance of UMKM Boba Drinks in Deli Serdang regency. Purchasing ability can moderate the influence of innovation on the marketing performance of UMKM Boba Drinks in Deli Serdang regency.